1996
DOI: 10.1021/jp9526509
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nonfluorescent Twisted Intramolecular Charge Transfer State on the Photophysical Behavior of Aminophthalimide Dyes

Abstract: Photophysical behavior of 4-aminophthalimide and its N,N-dimethyl derivative is studied in a series of solvents. A comparison of the fluorescence properties of the two compounds reveals that they behave quite differently despite their structural similarity. The efficient nonradiative decay of the dimethyl derivative in polar media is interpreted in terms of a nonemitting twisted state. Semiempirical calculations based on the AM1 method have been performed, and the results support the twisting mechanism. Calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
171
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(189 citation statements)
references
References 32 publications
15
171
0
3
Order By: Relevance
“…[52,[63][64][65] Clearly, this is a possibility here as indicated by behavior in NMR spectroscopic experiments at various temperatures. To investigate the large Stokes shifts observed for 12 and 13, the change to the conformation of 13 in its first singlet excited state relative to the ground-state structure was calculated.…”
mentioning
confidence: 87%
“…[52,[63][64][65] Clearly, this is a possibility here as indicated by behavior in NMR spectroscopic experiments at various temperatures. To investigate the large Stokes shifts observed for 12 and 13, the change to the conformation of 13 in its first singlet excited state relative to the ground-state structure was calculated.…”
mentioning
confidence: 87%
“…The linear relationship suggests the presence of just one excited state. These results indicated that the  e (dipole moment of 6 in the excited state) should be a little larger than the  g (the dipole moment of 6 in the ground state) because a positive solvatochromic effect was observed in the absorption spectra and emission spectra [51,52].…”
Section: Photophysical Propertiesmentioning
confidence: 91%
“…15 Thus, TMST was thought to be an appropriate compound to study the real viscosity of ionic liquid and the polarity of ionic liquid from the point of view of microviscosity and bulk viscosity. The measured viscosity of ionic liquid [bmim][PF 6 ] (260 cP) 16 used in these experiments as a solvent is much higher than that of acetonitrile (0.34 cP), 16 18 but is almost equivalent with the value of methanol (55.0). 18 In other words the viscosity of this ionic liquid is much higher than that of acetonitrile, but the polarity in E T (30) value is almost the same with that of alcohol and acetonitrile.…”
mentioning
confidence: 99%
“…The measured viscosity of ionic liquid [bmim][PF 6 ] (260 cP) 16 used in these experiments as a solvent is much higher than that of acetonitrile (0.34 cP), 16 18 but is almost equivalent with the value of methanol (55.0). 18 In other words the viscosity of this ionic liquid is much higher than that of acetonitrile, but the polarity in E T (30) value is almost the same with that of alcohol and acetonitrile. Figure 4 shows absorption, fluorescence, and fluorescence excitation spectra of trans-TMST in ionic liquid, [bmim] [PF 6 ].…”
mentioning
confidence: 99%